Research and contributions on improving the cyber security of the IT&C system of Permanent Electoral Authority - Dragomir, Adrian (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In order to respond effectively to the desire to constantly improve the electoral process, the Permanent Electoral Authority has undergone a series of administrative and regulatory change processes, in line with new trends in public administration management, namely simplification, dematerialization, digitization, staff professionalization, de-bureaucratization and decision transparency. The research report analyzes the institution's most important cyber security reforms in line with the new public sector models, and proposes a new security solution that is suitable to be integrated into the IT&C system of Permanent Electoral Authority.